New Zealand's engagement with the Five Ways to Wellbeing: evidence from a large cross-sectional survey. (3rd July 2019) - Mackay, Lisa; Egli, Victoria; Booker, Laura-Jane; Prendergast, Kate
ABSTRACT: The Five Ways to Wellbeing were developed in 2008 as a set of simple daily practices for individuals to improve their wellbeing. While there is some evidence to support the association between individual practices and wellbeing, it is unknown whether engaging in multiple practices – and in certain combinations – is associated with higher levels of wellbeing. A survey was undertaken with 10, 012 adults throughout Aotearoa, New Zealand, to assess individual wellbeing and participation in the Five Ways to Wellbeing (Connect, Give, Take Notice, Keep Learning and Be Active). Wellbeing was assessed with the Flourishing Scale ( Md = 46, IQR 39–49). Three objectives explored the cross-sectional association between the Five ways to Wellbeing and wellbeing: (1) multiple wellbeing practices and wellbeing, (2) clustering of multiple wellbeing practices, and (3) wellbeing practices as predictors of wellbeing. Results show that levels of wellbeing increased with each additional practice ( rho = .53, p < .001), regardless of the combination. However, the most important predictors of wellbeing were Keep Learning ( β = .23, p < .001) and Take Notice ( β = .22, p < .001). Studies investigating ways to increase participation in the Five Ways to Wellbeing are warranted to promote wellbeing in Aotearoa.